1993
DOI: 10.1002/app.1993.070481107
|View full text |Cite
|
Sign up to set email alerts
|

Transport characteristics and other physicochemical properties of aged poly(1‐(trimethylsilyl)‐1‐;propyne)

Abstract: Samples of poly[1–(trimethylsilyl)–1–propyne] were kept for about 4 years in ambient conditions. The permeability and diffusion coefficients were examined and found to be decreased by 1–2 orders of magnitude. To ascertain the nature of the changes underwent during long‐term storage of this polymer, several physicochemical methods were applied: positron annihilation, wide‐angle X‐ray diffraction, spin probe, and density evaluation. These studies indicated that a decrease of free volume and more close chain pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 19 publications
4
77
0
Order By: Relevance
“…This behavior is in accordance with Langmuir-type sorption, in which dissolved gas molecules fill in free volumes, leading to a reduction in the o-Ps intensities and lifetimes. These results are in accordance with previous results 6 in which the behavior occurred for the small holes as well as for the large ones. Using the data in Figure 2 the deduced CO 2 permeability is reduced to 5 ϫ 10 Ϫ7 , which agree with the value previously determined by these authors after CO 2 aging using the mass spectrometeric method.…”
Section: Resultssupporting
confidence: 95%
See 2 more Smart Citations
“…This behavior is in accordance with Langmuir-type sorption, in which dissolved gas molecules fill in free volumes, leading to a reduction in the o-Ps intensities and lifetimes. These results are in accordance with previous results 6 in which the behavior occurred for the small holes as well as for the large ones. Using the data in Figure 2 the deduced CO 2 permeability is reduced to 5 ϫ 10 Ϫ7 , which agree with the value previously determined by these authors after CO 2 aging using the mass spectrometeric method.…”
Section: Resultssupporting
confidence: 95%
“…This behavior occurs for the small holes as well as for the large ones. Such an increase after CO 2 or CH 4 desorption can be understood on the basis of the known instability 6 of PTMSP because of its low packing density and has already been reported 11 about many glassy polymers. The similarity in effect of CO 2 and CH 4 , which have almost equal sizes (0.029 nm 3 ), suggests that the increase in o-Ps formation is related to structural changes, which seem to be size dependent.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Large uncertainties in geometric density were reported for PTMSP: 0.71 Ϯ 0.07 g/cm 3 for as-cast films and 0.91 Ϯ 0.09 g/cm 3 for films aged for 4 years at ambient conditions. 16 Interestingly, the geometric density reported for as-cast PTMSP films varies from 0.61 to 0.81 g/cm 3 . 6,16 -20 The difference between these values is 0.20 g/cm 3 .…”
Section: Characterizationmentioning
confidence: 98%
“…Although ageing has been extensively investigated with respect to material properties, transport characteristics (Yampol'skii et al, 1993) have not often been studied. The relation of ageing to morphological features has been established several times (Montserrat & Cortes, 1995;Johansson & Tegenfeldt, 1993;Arnold, Leo & Tarjani, 1988), but to our knowledge no study of the ageing of PVDF has been reported.…”
Section: Introductionmentioning
confidence: 99%